2007 15th IEEE-NPSS Real-Time Conference 2007
DOI: 10.1109/rtc.2007.4382787
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of VxWorks, Linux, RTAI and Xenomai in a Hard Real-time Application

Abstract: We report on a set of performance measurements executed on VMEbus MVME5500 boards equipped with MPC7455 PowerPC processor, running four different operating systems: Wind River VxWorks, Linux, RTAI, and Xenomai. Some components of RTAI and Xenomai have been ported to the target architecture. Interrupt latency, rescheduling and inter-process communication times are compared in the framework of a sample real-time application. Performance measurements on Gigabit Ethernet network communication have also been carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 5 publications
0
35
1
5
Order By: Relevance
“…We can increase the DMA block transfer size to compensate the real-time deficiency and schedule uncertainty of Linux OS. Along with multicore processors, Linux with innovative kernel can fulfill this task more surely than some other general or embedded operating system [11]. Then there arises the problem of how to allocate large amounts of data in the Linux environment.…”
Section: Readout Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…We can increase the DMA block transfer size to compensate the real-time deficiency and schedule uncertainty of Linux OS. Along with multicore processors, Linux with innovative kernel can fulfill this task more surely than some other general or embedded operating system [11]. Then there arises the problem of how to allocate large amounts of data in the Linux environment.…”
Section: Readout Systemmentioning
confidence: 99%
“…Commercial off-the-shelf multi-core techniques and a new OS kernel optimized in real-time scheduling make engineers discuss and evaluate Linux solutions for the possibility of replacement of VxWorks, not only in industry, but also in scientific research [10,11]. Linux has been successfully applied to many real-time applications, even some hard real-time controls of scientific instruments [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…RTAI is already being successfully used in some fusion laboratories [5,6] but it was never tested on the multi-core x86 platform. As referred in the previous section a RTOS must guarantee low latency in response to hardware interrupts and a precise scheduling of the real-time tasks.…”
Section: Latency and Jitter Testsmentioning
confidence: 99%
“…In general, interrupt latency and rescheduling time should be considered for evaluating real-time performance. The performance measurements for the measured delays for VxWorks, Xenomai, RTAI and Linux have been addressed by Barbalace et al [17]. Therefore, measurements were concentrated on the performance for the effect of context switching in terms of the number of tasks running simultaneously for both real-time Linux and standard Linux.…”
Section: Implementation and Performance Measurementmentioning
confidence: 99%
“…Xenomai is a real-time development framework that cooperates with the Linux kernel in order to provide a pervasive, interface-agnostic, hard real-time support to user-space applications seamlessly integrated into the GNU/Linux environment. In performance measurements on four different OSs, Barbalace et al demonstrated that open-source software such as RTAI and Xenomai are suitable for hard real-time applications [17]. The open and modular approach that uses Xenomai over the IEEE 1394 real-time device driver has been described and its real-time performance has been evaluated for a mobile robot platform [18].…”
Section: Introductionmentioning
confidence: 99%